A Four-Component Domino Reaction: An Eco-Compatible and Highly Efficient Construction of 1,8-Naphthyridine Derivatives, Their In Silico Molecular Docking, Drug Likeness, ADME, and Toxicity Studies - Ankita Garg; Aschalew Tadesse; Rajalakshmanan Eswaramoorthy (Journal of Chemistry)
A multicomponent domino reaction of enaminone, malononitrile, and o-phthalaldehyde has been established, providing direct access to novel highly functionalized pentacyclic cyclopenta [b] indeno [1, 2, 3-de] [1,8] naphthyridine derivatives. The simplicity of execution, readily available substrates, high yields, excellent functional group tolerance, scalability, and good scores of environmental parameters make this synthetic strategy more sustainable and worthy of further attention. This one-pot transformation, which involved multiple steps and did not require the use of a catalyst, constructed four new C-C bonds, two new C-N bonds, and three new rings, with efficient use of all reactants. Furthermore, we performed in silico molecular docking analysis for prediction of anticancer (against human topoisomerase IIβ protein) and antimicrobial (against E.coli. DNA gyrase B protein) activities. Drug likeness and ADMET studies were also predicted. Overall investigation indicates that compound 6i may serve as a candidate that could be developed as potential anticancer and antimicrobial agent among all.